World Music : A Very Short Introduction - Bohlman, Philip V., 1952- (Oxford, New York Oxford University Press, 2002)
Attempts to draw readers into a range of historical encounters, in which music had the power to evoke the exotic and to give voice to the voiceless. This work helps the reader witness music's involvement in the modern world, but also the individual moments and particular histories that are crucial to an understanding of music's diversity.
Include Illustration, Reference, Map and Index
Keywords: World music -- World music--Analysis, appreciation